The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1289/ehp.97105s61611
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in radiation and health: reflections on the International Conference in Beer Sheva.

Abstract: Insofar as international conferences reflect the state of development of the subject under discussion, they provide an opportunity to question, at a rather fundamental level, the direction of and progress in the subject. With regard to the effects of radiation on health, many of the problems faced today, including uncertainties in the relationship between risk and dose and the origins of the psychosocial phenomena associated with many aspects of environmental radiation exposure, arise from a lack of adequate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…26 Many Russian-based studies also reported long-term psychological effects, but the scientific validity of these reports is difficult to evaluate. 1,[27][28][29] Although exposed children have an elevated rate of thyroid cancer and are a major focus of humanitarian organizations, no systematic mental health data exist. Four sources of evidence suggest that exposed children constitute a high-risk group for psychological impairment.…”
Section: Original Articlementioning
confidence: 99%
“…26 Many Russian-based studies also reported long-term psychological effects, but the scientific validity of these reports is difficult to evaluate. 1,[27][28][29] Although exposed children have an elevated rate of thyroid cancer and are a major focus of humanitarian organizations, no systematic mental health data exist. Four sources of evidence suggest that exposed children constitute a high-risk group for psychological impairment.…”
Section: Original Articlementioning
confidence: 99%